Degradation of MDEA in aqueous solution in the thermally activated persulfate system. Issue 6 (19th March 2017) - Li, Yong-Tao; Yue, Dong; Wang, Bing; Ren, Hong-Yang
ABSTRACT: The feasibility of methyldiethanolamine (MDEA) degradation in thermally activated PS system was evaluated. Effects of the PS concentration, pH, activation temperature and reaction time on MDEA degradation were investigated. Simultaneity, the thermodynamic analysis and degradation process were also performed. Several findings were made in this study including the following: the degradation rates of MDEA in thermally activated PS systems were higher than other systems. MDEA could be readily degraded at 40°C with a PS concentration of 25.2 mM, the process of MDEA degradation was accelerated by higher PS dose and reaction temperature, and MDEA degradation and PS consumption followed the pseudo-first-order kinetic model. The thermodynamic analysis showed that the activation process followed an endothermic path of the positive value of and spontaneous with the negative value of, high temperature was favorable to the degradation of MDEA with the apparent activation energy of 87.11 KJ/mol. Combined FT-IR with GC–MS analysis techniques, MDEA could be oxidative degraded after the C–N bond broken to small molecules of organic acids, alcohols or nitro compounds until oxidized to CO2 and H2 O. In conclusion, the thermally activated PS process is a promising option for degrading MDEA effluent liquor.